Towards sustainable construction solid waste management in Klang Valley, Selangor / Abdillah Bin Abdul Kadir - Abdul Kadir, Abdillah (Faculty of Architecture, Planning and Surveying, 2014)
Nowadays, the increasing quantity of construction solid waste has causes serious environmental problem which requires a better solution in handling the wastes that generate. Due to the overwhelming production of the wastes, the conventional method in handling construction solid waste seems to be irrelevant in ensuring sustainability for the waste management in the future For that reason, a proper way of handling construction wastes is significance in reducing the negative impacts towards the environment, social, and economy. Sustainable waste management is introduced to maintain the balance between the environment, social and economic aspects through several ways such as acts implementation, and techniques in managing waste. Therefore, it is essential to identify current waste management system adopted by industry in order to make adjustment and improvement in moving towards sustainable waste management. This paper highlights the current practice of the waste management system implemented in the country focusing in Klang Valley area and the restriction in applying the concept of sustainability into waste management through reviewing past similar researches. This research has conducted a structured interview with the local authorities and also an analysis survey with the selected G7 contractors in Klang Valley. The results obtained show the current waste management systems applied in Malaysia and factors that hinder the concept of sustainability into waste management. It allows a major shift in Malaysia waste management by improvise current waste management technology into more sustainable way.